Analisis Error Correction Model Analisis Error Correction Model terhadap Pengaruh Laju Pertumbuhan Ekonomi (LPE), Inflasi, dan Pengangguran pada Konsumsi Rumah Tangga di Sumatera Utara (2001–2021): Analisis Error Correction Model terhadap Pengaruh Laju Pertumbuhan Ekonomi (LPE), Inflasi, dan Pengangguran pada Konsumsi Rumah Tangga di Sumatera Utara (2001–2021) - Atika Zahra, Dwi; Irawan, Fais; Lejon Simamora, Kevin; Umi Al Mas, Khairunnisa; Erisa Aulia Sihotang, Sabrina; Nababan, Stevani; Mardiah, Siti; Sari Margaret Julianty Silaban, Putri (Universitas Jambi, 2025)
The primary component of aggregate demand, which represents both the stability of the local economy and the degree of community wellbeing, is household consumption. The purpose of this study is to examine how household spending in North Sumatra Province was affected by the Economic Growth Rate (LPE), inflation, and unemployment between 2001 and 2021. To assess both short-term and long-term correlations between variables, secondary data is analyzed using the Error Correction Model (ECM). According to the study's findings, long-term household consumption is positively and significantly impacted by LPE, indicating that economic expansion can raise people's purchasing power. In the meanwhile, both in the short and long term, unemployment and inflation have a detrimental but insignificant impact. A robust adjustment mechanism to the long-term balance is indicated by the significant correction coefficient of −0.969383. Therefore, it can be said that household spending in North Sumatra is mostly influenced by economic growth, with inflation and unemployment having comparatively little effect. The results of this research have implications for the importance of inclusive economic growth policies to strengthen household consumption, in line with achieving the Sustainable Development Goals (SDGs), especially Goal 1 (No Poverty) and Goal 8 (Decent Work and Economic Growth).